Galactan-binding antibodies. Diversity and structure of idiotypes (The Rockefeller University Press, 1983)
A group of eight IgM hybridoma proteins induced with beta(1,6)-D- galactan-containing antigens has been characterized in terms of primary amino acid sequence and idiotype expression. The H chain amino acid sequences reveal very strong homology in the VH segment although several substitutions are seen that suggest the occurrence of somatic mutation in these IgM molecules. Significant sequence variation was observed in CDR-3, the region generated by the D segment, and the two recombination events, VH-D and D-JH. The number of amino acids in this region contributed by the D segment was found to vary from two to six, yet the overall length of CDR-3 was precisely maintained by the addition of amino acids on either side of D during the recombination processes. These additional amino acids are suggested to result from nucleotide addition by repair enzymes. Idiotypic analysis of these proteins, in conjunction with an assessment of the H chain sequences, has permitted an identification of the molecular basis of both cross- reacting and unique idiotypic determinants expressed by these molecules.